Multiplex Cytokine Concentration Measurement: How Much Do the Medium and Handling Matter? - Luke Parkitny; James H. McAuley; Patrick J. Kelly; Flavia Di Pietro; Barbara Cameron; G. Lorimer Moseley (Mediators of Inflammation)
Cytokine concentrations are thought to be affected by methods of sampling and processing and by storage conditions. In this study we compared 17 cytokine concentrations obtained from plasma and serum at baseline and after a controlled thaw condition. We found that absolute agreement was poor between concentrations of cytokines in plasma and serum, except for MIP1β. A thaw condition significantly changed the concentrations of most cytokines, but serum appeared less affected by this than plasma was. Closer examination using Bland-Altman analyses revealed that for each comparison, agreement was moderately good for many cytokine concentrations. This is important because measures of agreement must be interpreted based on the required precision, which may differ between clinical and research demands. We also identified that for some cytokines, the relationship between serum and plasma is affected by concentration, thus advocating for the use of appropriate methods when performing such comparisons in studies such as systematic reviews and meta-analyses.